(untitled) - Fox, Stuart Ira (Boston, MA., 2006)
This book is a stand-alone human physiology manual that can be used in conjunction with any human physiology textbook. It includes a wide variety of exercises that support most areas covered in a human physiology course, allowing instructors the flexibility to choose those exercises best suited to meet their particular instructional goals. Background information that is needed to understand the principles and significance of each exercise is presented in a concise manner, so that little or no support is needed from the lecture text
Keywords: Human physiology,Sinh lý học người